ASSESSMENT OF THE ABILITY TO READ THE QUR'AN IN THE LEARNING OF THE QUR'AN AND HADITH AT STATE TSANAWIYAH MADRASAH 4 LANGKAT - Putri Ayu Riantika; Nurmawati (RADJA PUBLIKA, 2025)
This study aims to describe the types of assessments and techniques used in assessing the ability to read the Qur'an, the aspects tested in the ability to read the Qur'an in class VII-E, and how the assessment of the ability to read the Qur'an is carried out by the Qur'an Hadith teacher of class VII-E at MTs 4 Langkat in Qur'an Hadith learning. The research method used was descriptive qualitative. The data collection techniques used were observation and practical assessment techniques for reading the Qur'an, interviews, and documentation. All data obtained was then analyzed using the Miles and Huberman technique, which consists of data reduction, data presentation, and conclusion drawing. The results of the study showed that the students of MTs Negeri 4 Langkat class VII-E were divided into three groups of criteria, where there were students who were still in the stage of getting to know the Qur'an (iqro'), there were also students who were able to read the Qur'an but not fluently, and finally, there were students who were able to read the Qur'an well and correctly in accordance with the rules of reading the Qur'an.